2019
DOI: 10.14233/ajchem.2019.22156
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Constituents and Antiulcer Activity of n-Hexane Extract of Sanchezia nobilis Hook F. Leaves from Vietnam

Abstract: Five compounds (1-5) were isolated from the leaves of Sanchezia nobilis collected in Nam Dinh province by chromatographic methods. These compounds were identified as: mangiferin (1), β-sitosterol (2), margaric acid (3), ursolic acid (4), oleanolic acid (5). Their structures were elucidated by spectroscopic methods, including mass spectrometry and nuclear magnetic resonance. These compounds were isolated from the leaves of Sanchezia nobilis for the first time. Screening of gastric and duodenal antiulcer effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…In this work, phytosterols and kaempferol glycosides were detected only in stems. However, a recent work reported that phytosterols were isolated from n-hexane and ethylacetate extract of the leaves (Xuan et al, 2019a, while kaempferol glycosides were isolated from ethylacetate and aqueous extracts of leaves of S. nobilis (syn. S. oblonga) (Xuan et al, 2019b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this work, phytosterols and kaempferol glycosides were detected only in stems. However, a recent work reported that phytosterols were isolated from n-hexane and ethylacetate extract of the leaves (Xuan et al, 2019a, while kaempferol glycosides were isolated from ethylacetate and aqueous extracts of leaves of S. nobilis (syn. S. oblonga) (Xuan et al, 2019b).…”
Section: Discussionmentioning
confidence: 99%
“…An earlier study reported that S. nobilis extracts contain syringin, flavone glycosides, cinnamyl and benzyl alcohol glycosides, neolignan glucoside, besides matsutake alcohol glycosides (Ellah et al 2013(Ellah et al , 2014. The presence of the phytosterols daucosterol and stigmasterol, flavonol glycosides, scopoletin and 3'-O-methyl-3,4methylenedioxy ellagic acid in ethylacetate extract of the leaves of S. nobilis was reported recently (Xuan et al, 2019a. On the other hand, mangiferin, β-sitosterol, in addition to margaric, ursolic and oleanolic acids were isolated from n-hexane extracts (Xuan et al, 2019b), while 4',5,7-trihydroxy-3',5'-dimethoxyflavone and kaempferol glycosides were isolated from aqueous extracts of leaves (Loi et al, 2019b).…”
Section: Introductionmentioning
confidence: 85%